The Effect of Reproductive Health Education on “Bridge to Be” Knowledge in Pre-Marriage Preparation in the Working Area of Sukadami Public Health Center - Ai Sariningsih; Nofa Anggraini (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: This study aimed to determine the effect of reproductive health counseling on the bride and groom’s knowledge of pre-marital preparation. This research was conducted in the working area of the Sukadami Health Center, South Cikarang District. Methods: This study used quantitative analytical methods with a pre-experimental type of research with a one-group pretest-posttest design with a paired t-test statistical test. The research data collection used primary data taken directly from respondents using a questionnaire with a total sample of 52 respondents. Results: The results showed that of the 52 respondents studied, 33 respondents with good category reproductive health knowledge were found (63.46%), enough there were 16 people (30.77%) and there were 3 people (5.77%). The results of the t-test showed a p-value = 0.001, namely that there was a significant difference in the reproductive health knowledge of the bride and groom in pre-marital preparation in the Sukadami Primary health center work area before and after counseling was carried out. Conclusion: In connection with less knowledgeable respondents, 5.77% of extension workers are expected to provide unhurried counseling following the counseling SOP. Counseling with special needs counseling is provided with more quality.